FTIR Spectroscopic And Quantum Chemical Studies On Hydantoin - Boz, İsmail; Ünsalan, Ozan; ILDIZ, GÜLCE ÖĞRÜÇ (Maik Nauka/Interperiodica/Springer, 233 Spring St, New York, Ny 10013-1578 Usa, 2012)
In this study the geometry optimization of monomeric and dimeric forms (D1, D2, and D3) of hydantoin molecule were done using DFT method employing 6-31++G(d, p) basis set. Harmonic and anharmonic wavenumbers and infrared intensities were computed at the same theory level. Experimental IR spectrum was recorded in the region 400-4000 cm(-1). It has also been characterized by 1H and 13C NMR spectrum. The hydrogen bond (HB) interaction of hydantoin was analyzed via dimers of hydantoin. Detailed vibrational wavenumber shifts and all vibrational mode analyses were reported. Total energy distributions (TED, %) calculations were done to characterize the fundamentals.